The Use Of Technology In Citizenship Education Subjects As A Form Of Implementation Of Anti-Corruption Education In SMA N 12 Semarang - Risqi Yuliati; Ghanis Putra Widhanarto (Prosiding Seminar Nasional Pascasarjana, 2020)
The use of technology today is a mandatory action for the learning process. This research aims toknow the stages of application of technology and to know the application of anti-corruption educationvalues with the application of technology in Citizenship education subjects as a form ofimplementation of anti-corruption education at SMA N 12 Semarang. This research uses a qualitativemethod with data collection techniques used, namely observation, interview, documentation. Thisresearch uses constant comparative analysis. This research is the stage of application of technologyin Citizenship education subjects through two stages, namely the stage of determining activities andtechnological process stages. Teachers use simple e-learning 12 to apply teacher anti-corruptioneducation materials tucking in Citizenship education subjects to be delivered in the learning process.The values that arise in learners are ethical, discipline, responsibility, simplicity, hard work,independence, fairness, courage, caring already ingrained in the learner. This research contributes tothe field of management in the implementation of educational technology in schools.